Interaksi Personal Barista Dengan Konsumen Di Crematology Coffee Jakarta - Sugeng Wahjudi (Al-Maquro\': Jurnal Komunikasi dan Penyiaran Islam, 2022)
This study aims to find out and understand the importance of personal interaction between baristas and consumers, and to see how the communication process creates and affects consumer satisfaction, especially personal interactions between baristas and consumers at Krematology Coffee Jakarta. Researchers used qualitative research methods with case study methods. Data collection techniques using observation, interviews, and documentation. The theory used in this research is Social Exchange theory which examines that actions and decisions are based on perceptions of the costs or efforts that will be incurred, and the imbalance or feedback that will be obtained. The results showed that the average consumer was quite satisfied with the services provided by the barista at Crematology Coffee, in accordance with the procedure or SOP, the barista was ready and welcome, and also interactive communication made by the barista in the form of responsive and communicative actions directly with consumers.